Recent Medical Graduates’ Abilities in Carrying Out Consultations with Patients: Views of Interns, Medical teachers, and Medical Graduates (Bangladesh Journal of Medical Education, 2023)
This descriptive type cross sectional study was carried out to explore the views of medical teachers, medical graduates and intern doctors regarding ability of recent graduates on consultation with patients.  Study period was from January 2021 to December 2021. The study was carried out in twelve government, private and army medical colleges across Bangladesh. Sample size total 636 medical teachers, medical graduates and intern doctors. Convenience sampling technique was adopted in selecting medical college and purposive sampling technique is adopted for respondent in this study. Data were collected by self administered semi structured questionnaire and data were then compiled and analyzed using SPSS version 26.  Among 636 participants, majority were intern doctors (39.3%) followed by 33.8% medical graduates and teachers (26.8%). Majority of the respondents were from government medical college i.e., 51.8% followed by 30.1% from private medical college and 18.2 % from army medical college.  Study revealed that all respondents (Medical teachers, medical graduates and intern doctors) agreed that for consultation with patients, recent medical graduates are more prepared in taking history and physical examination; but least prepared in breaking bad news. Majority of the all three participants’ teachers, medical graduated and intern doctors had provided a mild positive agreement about the recent medical graduates’ patient consultation skill. None of them had given strongly positive agreement about recent medical graduates’ ability on patient consultation skill. Further research needed to generalize this study finding.Bangladesh Journal of Medical Education Vol.14(1) January 2023: 26-34